Relationship between directors’ bonus and shareholders’ value: a view of corporate governance / Akhma Adlin Khalid, Zubaidah Zainal Abidin and Norashikin Kamarudin. - Khalid, Akhma Adlin; Zainal Abidin, Zubaidah; Kamarudin, Norashikin (Universiti Teknologi MARA Cawangan Selangor, 2012)
Directors’ remuneration research has traditionally focused on total salary, cash compensation and long–term incentives plans. Consequently, a systematic study on short–term annual bonus is lacking. To address this omission, this study is conducted to investigate the trend of bonus received by the executive directors among Malaysian companies publicly listed on Bursa Malaysia in the current economic condition from 2008 to 2010. The study also examines the relationship between the executive directors’ bonus and shareholders’ value, specifically defined by firm performance, as measured using stock return (SR) and earning per share (EPS) and by firm size, as measured using the total number of employee, so as to test the practice of the principle corporate governance among the Malaysian listed companies from two different theories, i.e. agency theory and power theory. For firm performance, the findings support the agency theory since directors’ bonus is found to be positively associated with firm performance, as measured by EPS. However, the findings found no significant relationship between directors’ bonus and stock return. For firm size, the findings support both theories since directors’ bonus is found to be positively associated with firm performance as measured by total sales and negatively associated with firm size as measured by total number of employee. Consistent with the previous studies on executive bonuses, this association remains weak. However, power theory revealed that weak governance may foster the rise of powerful directors and thus, weaken the corporate governance value in a company. Therefore, it is suggested that close monitoring of directors’ remuneration should continue and shareholders should remain extra vigilant.